In reference to the correlation of acts which are described by art. 238–241 of the Criminal Code of the Republic of Belarus - Zakhilko, Kiryl S. (Journal of the Belarusian State University. Law, 2021)
The content of art. 238–241 of the Criminal Code of the Republic of Belarus from the point of view of the systemic correlation between themselves is analysed. The main positions on the ratio of art. 238 and 240 of the mentioned code are reviewed and evaluated. The problematic field of the inconsistency of art. 240 and art. 239, 241 of the code is formulated. Based on the generalisation of the data obtained, a version of a consistent definition in the Criminal Code of the Republic of Belarus of the acts related to criminal bankruptcy is proposed.
Keywords: criminal bankruptcy; bankruptcy; bankruptcy law; insolvency; criminal bankruptcy norm system